Defining the Core Proteome of the Chloroplast Envelope Membranes - Simm, Stefan; Papasotiriou, Dimitri; Ibrahim, Mohamed; Leisegang, Matthias; Müller, Bernd; Schorge, Tobias; Karas, Michael; Mirus, Oliver; Sommer, Maik; Schleiff, Enrico (Frontiers in Plant Science, 2013)
High-throughput protein localization studies require multiple strategies. Mass spectrometric analysis of defined cellular fractions is one of the complementary approaches to a diverse array of cell biological methods. In recent years, the protein content of different cellular (sub-)compartments was approached. Despite of all the efforts made, the analysis of membrane fractions remains difficult, in that the dissection of the proteomes of the envelope membranes of chloroplasts or mitochondria is often not reliable because sample purity is not always warranted. Moreover, proteomic studies are often restricted to single (model) species, and therefore limited in respect to differential individual evolution. In this study we analyzed the chloroplast envelope proteomes of different plant species, namely, the individual proteomes of inner and outer envelope (OE) membrane of Pisum sativum and the mixed envelope proteomes of Arabidopsis thaliana and Medicago sativa. The analysis of all three species yielded 341 identified proteins in total, 247 of them being unique. 39 proteins were genuine envelope proteins found in at least two species. Based on this and previous envelope studies we defined the core envelope proteome of chloroplasts. Comparing the general overlap of the available six independent studies (including ours) revealed only a number of 27 envelope proteins. Depending on the stringency of applied selection criteria we found 231 envelope proteins, while less stringent criteria increases this number to 649 putative envelope proteins. Based on the latter we provide a map of the outer and inner envelope core proteome, which includes many yet uncharacterized proteins predicted to be involved in transport, signaling, and response. Furthermore, a foundation for the functional characterization of yet unidentified functions of the inner and OE for further analyses is provided.